Quercetin alleviates endothelial dysfunction in preeclampsia by inhibiting ferroptosis and inflammation through EGFR binding - Meiting Shi; Lu Sun; Jiachun Wei; Yao Shen; Jian Wang; Ping Zhang; Xiaofeng Yang; Yuzhen Ding; Wanchang Yin; Xinyao Lu; Xuesong Yang; Guang Wang; et al. (Communications Biology)
Abstract Preeclampsia (PE) is a pregnancy-specific complication and there remains no effective treatment. Given the limitations on medication use during pregnancy, exploring natural, safe, and effective drugs for PE is worthwhile. We investigate the causal relationship between ferroptosis, inflammation, and PE, and determine the protective effects of quercetin (QCT), a representative compound that is classified as a flavanol, against endothelial dysfunction. Then, the target of QCT is predicted and verified. The prophylactic addition of a low dose of QCT rescues endothelial dysfunction, aiding in endothelial repair. Furthermore, QCT alleviates PE-like maternal manifestations and endothelial dysfunction in the placenta of the selective reduced uteroplacental perfusion (sRUPP) rat model through binding to the epidermal growth factor receptor (EGFR). The potential applications of QCT are expanded, offering the possibility of further development as a safe and effective preventive molecule for PE.